2023
DOI: 10.3389/fneur.2023.1094364
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of the pretreatment systemic immune-inflammation index in patients with glioma: A meta-analysis

Abstract: BackgroundThe systemic immune-inflammation index (SII) has been recognized as the indicator that reflects the status of immune responses. The SII is related to the prognostic outcome of many malignancies, whereas its role in gliomas is controversial. For patients with glioma, we, therefore, conducted a meta-analysis to determine if the SII has a prognostic value.MethodsStudies relevant to this topic were searched from 16 October 2022 in several databases. In patients with glioma, the relation of the SII level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…In recent years, numerous meta-analyses have demonstrated that the SII is of great significance TherapeuTic advances in hematology in predicting the prognosis of various solid tumors. [31][32][33][34][35] Zhang et al 31 demonstrated that a higher SII indicated poor OS and PFS in glioma cases in their meta-analysis that included eight articles. As revealed by Zeng et al, 35 a high SII remarkably predicted poor OS and PFS in patients with NPC in a meta-analysis comprising 2169 subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, numerous meta-analyses have demonstrated that the SII is of great significance TherapeuTic advances in hematology in predicting the prognosis of various solid tumors. [31][32][33][34][35] Zhang et al 31 demonstrated that a higher SII indicated poor OS and PFS in glioma cases in their meta-analysis that included eight articles. As revealed by Zeng et al, 35 a high SII remarkably predicted poor OS and PFS in patients with NPC in a meta-analysis comprising 2169 subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, numerous meta-analyses have demonstrated that the SII is of great significance in predicting the prognosis of various solid tumors. 3135 Zhang et al. 31 demonstrated that a higher SII indicated poor OS and PFS in glioma cases in their meta-analysis that included eight articles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognostic/predictive power of NLR may be further improved by combining NLR assessment with other biomarkers. According to recent meta-analyses and systematic reviews, absolute/total lymphocyte count (ALC/TLC, especially post-treatment) ( 321 ), platelet-to-lymphocyte ratio (PLR) ( 133 , 322 ), lymphocyte-to-monocyte ratio (LMR) ( 323 ), systemic immune-inflammation index (SII), calculated by platelet count×neutrophil count/lymphocyte count ( 129 , 324 ), and systemic immune response index (SIRI), calculated by neutrophil count×monocyte/lymphocyte count ( 325 327 ) are the emerging prognostic factors in glioblastoma/glioma. In a retrospective study, Yang et al.…”
Section: Future Directionsmentioning
confidence: 99%
“…Inflammation is a pivotal factor in the advancement of critical illnesses and is frequently linked with ARDS, consequently elevating the mortality risk [ 17 , 18 ]. ystemic immune-inflammatory index (SII) was initially characterized as a potential biomarker or the assessment of tumor proliferation and cardiovascular disease pathogenesis [ [19] , [20] , [21] ].SII was calculated as platelets count x neutrophils count/lymphocytes count, and it is now considered to reflect inflammation status better [ 22 , 23 ].The SII has been effectively used to evaluate prognosis in patients suffering from various conditions, including stroke [ 24 ] and cancer [ 25 ]. However, the correlation between SII and the prognosis of patients with ARDS is still not well-established and warrants further exploration.…”
Section: Introductionmentioning
confidence: 99%